Phosphorylation of the nonstructural proteins encoded by three avian acute leukemia viruses and by avian fujinami sarcoma virus. - Bister, K (1980)
The gag gene-related, nonstructural proteins of three avian acute leukemia viruses (namely, myelocytomatosis viruses MC29 and CMII and avian erythroblastosis virus) and of avian Fujinami sarcoma virus (FSV) isolated by immunoprecipitation from cellular lysates with anti-gag serum were shown to be phosphoproteins in vivo. The specific 32P radioactivity of the nonstructural proteins of MC29, CMII, and FSV was significantly higher than that of helper viral, intracellular gag proteins. Two of these proteins, i.e., the 140,000-dalton FSV and the 110,000-dalton MC29 proteins, were also phosphorylated in vitro by a kinase activity associated with immunocomplexes. This kinase activity is either separated from these proteins or inactivated by incubation of cellular lysates with normal serum followed by adsorption to staphylococcal protein A or sedimentation at 100,000 x g or both. It remains to be resolved whether the 110,000-dalton MC29 and 140,000-dalton FV proteins, in addition to being substrates for phosphorylation, also have intrinsic kinase activity.